LOMOGRAFI SEBAGAI EKSPRESI SENI DAN GAYA HIDUP LOMOGRAPHIC SOCIETY SOLO - Wahyudi, Johan Ies (Institut Seni Indoensia Surakarta, 2016)
The aim of this study is to investigate the phenomenon of Lomography as art and lifestyle at the Lomography community in Surakarta. The subjects were community Solo Lomographic Society and the object of research is the works Lomografi of the community. Collecting data in this study using the method of observation, literature / documents and interviews. Observations carried out on community activities Lomographic Society Solo in Surakarta and artifacts of their activities such as exhibition catalogs and documents activities. A literature study to strengthen the theoretical foundation and a variety of matters relating to Lomography. Interviews were conducted to speakers who are competentas a practitioner Lomografi, photographic art expert and journalist who has written about the phenomenon Lomografi in Indonesia. The target of this research is knowing the stages in the process of creating works Lomografi and aesthetic form of artwork Lomografi the aesthetic point of view of art‘as well as the internal-external factors that encourage the formation of community of Lomographic Society Solo and existence.Keywords: LOMO, Lomografi, Lomographic Society Solo, art expression, lifestyle.